Cancer-associated fibroblasts in osteosarcoma: key players in immune escape and targeted therapy - Fan, Junjie; Jin, Yujie; Lv, Feng; Wu, Weidong; Sun, Li; Wang, Churong (Frontiers in Immunology, 2025)
Osteosarcoma represents the most common principal malignant bone tumor that predominantly appears among teenagers and children. While multimodal treatment methods have greatly evolved with time, survival for recurrent or metastatic disease remains low due to the resistance that accumulates during treatment. Increasing evidence identifies the tumor microenvironment (TME), in particular cancer-associated fibroblasts (CAFs), as playing an important role in imposing immune suppression, enhancing tumor aggressiveness, and mediating resistance toward immunotherapy and chemotherapy. This article gives an overview of the derivation, phenotypic heterogeneity, and mechanisms of action of CAFs during osteosarcoma, such as facilitating immune escape, survival signaling, drug efflux, regulation of genes through exosomes, and inhibiting ferroptosis. Furthermore, we present existing and new treatment methods that are centered on CAFs, such as suppression of the paracrine pathway (e.g., IL-6/STAT3, TGF-β), depletion of CAFs lineages by targeting fibroblast activation protein (FAP), and conversion toward tumor-restraining CAFs. Other methods that are gaining popularity are targeting CAFs-releasing exosomes and metabolic liabilities. By shedding light on CAFs-based methods for imposing resistance and trying targeted treatments, this review offers insights into novel therapeutic combinations that can overcome treatment barriers and improve survival outcomes in osteosarcoma regimens.